SYSTEMATIC DIAGNOSTIC APPROACH IN THE ACUTE PHASE OF MYOCARDIAL INFARCTION - I. E. Belaya; B. Yu. Dobrin; V. I. Kolomiets (Российский кардиологический журнал, 2011)
Atypical clinical course of myocardial infarction (MI) is used as an example, in order to demonstrate the benefits of systematic diagnostic approach in the acute MI phase. A new cardiac diagnostic complex, using the modern information technologies, allows automatic calculation of vector electrocardiogram (VECG) loop parameters, as well as detailed analysis of specific VECG parts magnified 3000 times. VECG method, as an addition to standard ECG, demonstrated myocardial damage in the reciprocal zone, disturbed conductivity and repolarisation, and cardiac overload, which gave an opportunity to specify the degree and the spread of pathological changes in the myocardium.